Advances in Human Immune System Mouse Models for Studying Human Hematopoiesis and Cancer Immunotherapy - Mian, Syed A.; Anjos-Afonso, Fernando; Bonnet, Dominique (Frontiers in Immunology, 2021)
Immunodeficient mice reconstituted with human immune cells offer a unique opportunity to comprehensively study human hematopoiesis, infectious disease, autoimmunity, and tumour immunity in vivo. Recent progress in xenograft mouse models in which recipient immunodeficient mice carry several gene mutations or overexpress human cytokines and self-recognition molecules, have improved human hematopoietic stem and progenitor cell engraftment as well as created more functional immune cell development in primary and secondary lymphoid tissues. In addition, several new approaches to modify or to add human niche elements to further humanize immunodeficient mice have allowed a more precise characterization of human hematopoiesis. These important refinements have opened the possibility to evaluate not only human immune responses to different tumour cells but also to investigate how malignant cells interact with their niche and most importantly to test immunotherapies in a more pre-clinically relevant setting.